On Omega polynomial of Cartesian product graph - Ghorbani M.; Hosseinzadeh M.A.; Diudea M.V. (Utilitas Mathematica, 2011)
A new counting polynomial, called Omega, was recently proposed by Diudea. It is defined on the ground of opposite edge strips "ops". The Sadhana polynomial has been defined to evaluate the Sadhana index of a molecular graph. A third one, called Theta polynomial is also derived from ops. In this paper we compute Omega, Sadhana and Theta polynomials of the Cartesian product graphs.